The Behavior of Postpartum Mothers and Acehnese Families in Postpartum Care at Beutong Health Center, Naganraya Regency, Aceh Province in 2024 - Febriana Sari; Fadilla Sutia; Siti Nurmawan; Lisa Putri Utami Damanik; Dyanti SR Butarbutar; Sitti Nuraisyah; Enamari Enamari (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The postpartum period is a critical time for both the mother and newborn, where healthcare is essential to avoid the risk of mortality. This study aims to analyze the behavior of postpartum mothers and Acehnese families in postpartum care at the Beutong Health Center, Nagan Raya Regency in 2024. A quantitative research method with a descriptive design was used, and the sampling technique applied was total sampling, with a population of 40 postpartum mothers. Data collection was carried out through interviews using a questionnaire. The results showed that 77.8% of mothers and families were aware of the nutrition needed for postpartum mothers, 58.3% understood the process of uterine involution, and 100% of postpartum mothers knew daily activities to accelerate recovery. The family's supportive attitude towards postpartum care was evident in their dietary recommendations, such as providing vegetables (83.3%) and fish (80.5%), forbidding the mother from leaving the house (100%), and administering algae (88.9%). However, 30.6% of postpartum mothers did not consume vegetables regularly. These findings highlight the importance of improving family understanding and support in postpartum care to accelerate the recovery of mothers and babies. The implication of this research is expected to improve postpartum care programs at Beutong Health Center.